'Saving the Nation's Mothers': The Problem of Maternal Mortality, 1919-1940 - Vock, Jane (My University, 1983)
The high number of maternal deaths in the 1920s and 1930s, and the attempts to alleviate this problem, represents an important segment in the history of childbirth. Although the issue of maternal health care has been examined in relation to other countries, such as England and the United States, it has received little scholarly attention in Canada. This thesis is an examination of this one segment in the history of childbirth. Maternal mortality was the second leading cause of death for women of childbearing age during the 1920s and 1930s in Canada. In 1928 alone, over 1500 women died in childbirth. The central concern in this thesis is how the problem of maternal mortality was defined and resolved in Canada, with an empirical focus on Ontario. The activities and involvement of the medical profession and state officials provide the major focus of attention. State officials were primarily responsible for the medicalization of the problem of maternal deaths, and concomitantly, played a crucial role in the medicalization of pregnancy and childbirth. The findings in this work contrast with previous analyses of the history of childbirth, in that the majority of practitioners were apathetic to the problem of maternal mortality, and were reluctant to extend their control over obstetrical care to include all classes of women. The profession did not seriously address the issue of maternal health care until they anticipated a crisis in their legitimation. The findings are congruent with previous analyses in that it was found that physicians were responsible for a number of maternal deaths because of their excessive and unsanitary interference with labour and delivery.
The Problem of Maternal Mortality, 1919-1940
Keywords: mother; mortality; 1919-1940